Plant Rabs and the role in fruit ripening - Lawson, Tamunonengiyeofori; Mayes, Sean; Lycett, Grantley W.; Chin, Chiew Foan (Taylor & Francis, 2018)
Fruit ripening is a complex developmental process that involves the synthesis and modification of the cell wall leading up to the formation of an edible fruit. During the period of fruit ripening, new cell wall polymers and enzymes are synthesized and trafficked to the apoplast. Vesicle trafficking has been shown to play a key role in facilitating the synthesis and modification of cell walls in fruits. Through reverse genetics and gene expression studies, the importance of Rab guanosine triphosphatases (GTPases) as integral regulators of vesicle trafficking to the cell wall has been revealed. It has been a decade since a rich literature on the involvement of Rab GTPase in ripening was published. Therefore, this review sets out to summarize the progress in studies on the pivotal roles of Rab GTPases in fruit development and sheds light on new approaches that could be adopted in the fields of postharvest biology and fruit-ripening research.